A Puzzle about ‘if’, Update and Compositionality - Böhm, Mathias (Proceedings of Sinn und Bedeutung, 2024)
According to dynamic approaches to meaning, meanings are context change potentials: ways in which an assertion of a sentence affects the context or the common ground of a conversation. In this paper I will argue that it is not straightforward to square the idea that meanings are context change potentials with an adequate theory of the discourse dynamics of conditionals and the idea that meanings are compositional. As I will argue, there is a tension between providing a prima facie plausible theory of the discourse dynamics of indicative conditionals while holding on to a popular and widespread notion of what it is for meanings to be compositional. The tension disappears, if we reject the view that meanings are context change potentials. That said, I will close the paper by discussing what I take to be the two most promising routes defenders of a dynamic approach to meaning could take in order to resolve the tension.